Práticas de marketing verde e comportamento de consumo verde no mercado de cosméticos: o papel das características demográficas - Seixas, Maria Eduarda de Andrade (Brasil, 2024)
This study investigates the influence of demographic characteristics on green consumer behaviour and green marketing practices in the cosmetics market. Demographic variables such as age, gender, level of education and income were considered. The research was conducted using an online questionnaire, adapted from Menhaj et al. (2023), using the survey technique. Inferential tests were carried out to test the hypotheses formulated, such as ANOVA and t-test. The results indicate that there are no significant differences in the average scores of consumers in relation to green marketing practices and green consumption behaviour based on the variables, suggesting that, regardless of their demographic characteristics, consumers respond in a similar way to green marketing practices in the cosmetics sector.